2009
DOI: 10.1007/s10452-009-9275-2
|View full text |Cite
|
Sign up to set email alerts
|

Radiation transfer and heat budget during the ice season in Lake Pääjärvi, Finland

Abstract: Lake Pääjärvi, a boreal Finnish lake, was investigated in winter for weather conditions, structure and thickness of ice and snow, solar radiation, and under-ice current and temperature. Heat budget of Lake Pääjärvi in January-March was governed by terrestrial radiation losses of 20-35 W m -2 recompensed by ice growth of 0.5-1.0 cm day -1 . In April, snow melted, albedo decreased from 0.8 to \0.1, and the mean ice melt rate was 1.5 cm day -1 . Internal melting and surface melting were about equal. The mean turb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
96
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(113 citation statements)
references
References 25 publications
16
96
1
Order By: Relevance
“…The increasing heat accumulated in the water of Morskie Oko has also resulted in shorter ice cover duration - [29] assessed as having decreased by 10 days·dec -1 . The relationship between heat content and ice cover has been described in the example of Lake Pääjärvi in southern Finland [30]. Those data might be useful for further studies on processes determining lake dynamics.…”
Section: Discussion Of Resultsmentioning
confidence: 97%
“…The increasing heat accumulated in the water of Morskie Oko has also resulted in shorter ice cover duration - [29] assessed as having decreased by 10 days·dec -1 . The relationship between heat content and ice cover has been described in the example of Lake Pääjärvi in southern Finland [30]. Those data might be useful for further studies on processes determining lake dynamics.…”
Section: Discussion Of Resultsmentioning
confidence: 97%
“…During this period, vertical melt channels spanning the ice layer form between black ice crystals with horizontal c axes and tend to grow larger as melt progresses, facilitating the transport of water and trapped gas (Browman, 1974). The absorption of solar radiation within the ice layer accelerates this process, particularly after the high-albedo snow cover has melted completely (Williams, 1969;Ashton, 1986;Jakkila et al, 2009), as does the presence of ice-trapped bubbles (our observation when harvesting ice blocks; A. Bondurant, personal communication, 2014).…”
Section: Release Of Ice-trapped Bubblesmentioning
confidence: 82%
“…(2) and (3) are invalid for T air > 0, which was the case on 4 consecutive days in October 2010 after freeze-up, but we applied this model as an approximation. Previous studies of melting ice found the formation of channels within lake ice instead of decreasing thickness (e.g., Browman, 1974;Nye, 1989;Jakkila et al, 2009), so we assume zero ice growth around trapped bubbles during this period.…”
Section: Ice Growthmentioning
confidence: 99%
“…The heat flux from lake water to the ice bottom has been earlier examined in the nearby Lake Pa¨a¨ja¨rvi by Shirasawa et al (2006) and Jakkila et al (2009). The magnitude was found to be 3Á10 W m (2 based on field data.…”
Section: Seasonal Study For the Winter 2008á2009mentioning
confidence: 98%